A Comprehensive Assessment of Various Converter Topologies for Electric Vehicle and Grid Integration - Sharma, Yogendra Kumar; Kidwai, Mohd. Suhaib; Husain, Mohammed Aslam; Ansari, Akhtar Saleem; Kumar, Navneet; Bakhsh, Farhad Ilahi (Recent Advances in Electrical & Electronic Engineering, 2025)
The emergence of Vehicle-to-Grid technology presents an encouraging frontier, enabling electric vehicles (EVs) to work as energy resources for various resident appliances, thereby playing crucial roles in peak load management, power stability, and balancing the load. Vehicle-to-grid hinges on both directions of power flow between the Electric Vehicle batteries and AC grid, facilitated by converters having bidirectional electronics power. This study undertakes a comprehensive investigation of various power factor correction (PFC) devices and various converter (DC to DC) topologies tailored for Vehicle to Grid or Grid to Vehicle operations. A detailed comparison of THD, efficiency, and power level of various topologies has been presented in this paper. The observations based on the comparative analysis have also been given. Additionally, through a detailed analysis, considering factors such as efficiency and THD, this study aims to guide the selection of suitable bidirectional chargers, thus serving as a valuable resource for decision-makers in the Electric Vehicle domain.
Keywords: electric vehicle